Remark
Break this down into smaller steps. Do as much as you can before considering the next part.
Step One
multiply (6*10^5) * (5 * 10^-9)
5 * 6 = 30
10^5 * 10-9 = 10^(5 - 9) = 10^-4
30 * 10^-4. But scientific notation expresses numbers between 1 and 10
30 * 10^-4 = 3 * 10^1 * 10^-4 = 3 * 10^(1 -4) = 3 * 10^-3
That's about as far as you can go with this step.
Step Two
Divide 3*10^-3 by 3 * 10^-3
When you divide anything at all by itself, you get 1.
For example 130011 / 130011 = 1
So
3 * 10^-3 divided by 3*10^-3 = 1
Answer: 1